Tourism Attraction, Facilities, Flow and Assessment of Tourism Product of Manaslu Conservation Area - Baral, Chandra Kanta; Neupane, Basanta Kumar (The Geographic Base, 2020)
This study aimed to understand the tourist attractions, major tourism products and their assessment in Manaslu Conservation Area of Nepal MCA). MCA is a place well known both, nationally and internationally, for its scenic beauty, unique ecology, and rich cultural heritage, given by its geographic position and unique topography. The number of tourists visiting this area has been increasing every year. In 2001 the tourist flow was only 798 whereas in 2019 it was 7655. Such tourism growth has several socio-economic and cultural consequences. Along with the increased number of tourists, tourism focused facilities and infrastructures like hotels and tea shops are also increasing in the area. There are 127 hotels with 1328 rooms and 2827 beds (as of 2019) providing food and accommodation services for the visitors. However, even though there are many potential areas for tourism development in the Manaslu Conservation Area, because of less promotional practices, there is very little tourism activity in the region. With the area's diverse physiography, unique landscape, biodiversity and the social-cultural dimension of the villages, the area could provide plenty of attractions for tourism.